2001
DOI: 10.1074/jbc.m102780200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Phosphatase 2A Overrides Tau Protein Kinase I/Glycogen Synthase Kinase 3β and Cyclin-dependent Kinase 5 Inhibition and Results in Tau Hyperphosphorylation in the Hippocampus of Starved Mouse

Abstract: Hyperphosphorylated tau is the major component of paired helical filaments in neurofibrillary tangles found in Alzheimer's disease (AD) brain. Starvation of adult mice induces tau hyperphosphorylation at many paired helical filaments sites and with a similar regional selectivity as those in AD, suggesting that a common mechanism may be mobilized. Here we investigated the mechanism of starvation-induced tau hyperphosphorylation in terms of tau kinases and Ser/Thr protein phosphatases (PP), and the results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 70 publications
12
159
2
Order By: Relevance
“…Previous reports demonstrating that modulations of glucose or insulin levels alter tau antigenicity in neuronal cultures support this hypothesis (Cheng and Mattson, 1992;Hong and Lee, 1997;Lesort et al, 1999). We also reported that starvation, which decreases the amount of circulating glucose and insulin and lowers glucose utilization (Newsholme, 1976;Cherel et al, 1988), induces AD-like tau hyperphosphorylation in mice (Yanagisawa et al, 1999;Planel et al, 2001).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Previous reports demonstrating that modulations of glucose or insulin levels alter tau antigenicity in neuronal cultures support this hypothesis (Cheng and Mattson, 1992;Hong and Lee, 1997;Lesort et al, 1999). We also reported that starvation, which decreases the amount of circulating glucose and insulin and lowers glucose utilization (Newsholme, 1976;Cherel et al, 1988), induces AD-like tau hyperphosphorylation in mice (Yanagisawa et al, 1999;Planel et al, 2001).…”
Section: Introductionmentioning
confidence: 75%
“…Starvation was performed as reported previously (Planel et al, 2001). To investigate the effect of glucose, food was similarly withheld from four mice, but they had free access to a 30% glucose solution.…”
Section: Alterations Of Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…1E) in JNPL3 mice (n ϭ 6 for each treatment). PBS was used for control rather than NaCl because our published data have shown that NaCl has no significant effect on tau phosphorylation (29). Furthermore, the use of a second GSK-3 inhibitor strengthened our confidence that the effects seen with LiCl were not due to ionic imbalance.…”
Section: Resultsmentioning
confidence: 99%
“…We interpret these changes in the activation state of this kinase isoforms as not relevant to the increase in tau phosphorylation we observed under our experimental conditions as it is known that an increase in pGSK3 is an index of a reduced activity of this kinase (Fang et al ., 2000). For this reason, we believe that, as previously reported, the change in pGSK3 in our cells is a generic response to an energy‐deprived condition (Planel et al ., 2001). …”
Section: Discussionmentioning
confidence: 99%